PERMAINAN TRADISIONAL CUBLAK-CUBLAK SUWENG DARI PROVINSI YOGYAKARTA DAN PEMBENTUKAN KARAKTER TANGGUNG JAWAB PADA PESERTA DIDIK MI/SD DI INDONESIA - Yosie Ervanda; Anis Fuadah Z (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2020)
The purpose of this study was to see the traditional cublak-cublak suweng game from D.I Yogyakarta, and the order for the character of responsibility for students. Knowing the method of implementing the cublak-cublek suweng game that can shape the character of responsibility for students. This research method is research research. The research subjects were research articles and web that discussed the cublak-cublak suweng game that could be accounted for for its authenticity and correctness. The scope of this research includes elementary school teachers, elementary school children, and the surrounding community who are familiar with this game, as well as the role of the government in preserving the cublak-cublak suweng game and applying it to elementary schools at this time.This research was conducted to explain whether the cublak-cublak suweng game in the present era can give pleasure after being played and the impact that occurs after being played 1) Introduction to what cublak-cublak suweng is and how to play it. 2) Implementation of the cublak-cublek suweng model that can develop the character of responsibility for students, 3) The effectiveness of the cublak-cublak suweng game in shaping the character of responsibility for students. 4) what are the effects if you continue to drink it again and again.